2022
DOI: 10.3389/fmolb.2022.849979
|View full text |Cite
|
Sign up to set email alerts
|

Structural Dissection of the First Events Following Membrane Binding of the Islet Amyloid Polypeptide

Abstract: The islet amyloid polypeptide (IAPP) is the main constituent of the amyloid fibrils found in the pancreas of type 2 diabetes patients. The aggregation of IAPP is known to cause cell death, where the cell membrane plays a dual role: being a catalyst of IAPP aggregation and being the target of IAPP toxicity. Using ATR-FTIR spectroscopy, transmission electron microscopy, and molecular dynamics simulations we investigate the very first molecular steps following IAPP binding to a lipid membrane. In particular, we a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 96 publications
(140 reference statements)
0
8
0
Order By: Relevance
“…Here, we discovered that the hydrophobic amino acids, L16 and I26, (see Figure 4 and Figure 5 ), are the major lipid binding residues of hIAPP oligomers on Lod and PS-cluster nanodomains on both the CO-raft and PS-raft. The N -terminal region (residues 1 to 20) containing residue L16 of structured hIAPP has been implicated in various experimental and computational studies [ 24 , 26 , 34 , 35 , 36 ]. In this study, we discovered that residue I26, associated with the C terminus (residues 21 to 31), which contains the fibril core of hIAPP fiber, represents an extra binding region for disordered oligomers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we discovered that the hydrophobic amino acids, L16 and I26, (see Figure 4 and Figure 5 ), are the major lipid binding residues of hIAPP oligomers on Lod and PS-cluster nanodomains on both the CO-raft and PS-raft. The N -terminal region (residues 1 to 20) containing residue L16 of structured hIAPP has been implicated in various experimental and computational studies [ 24 , 26 , 34 , 35 , 36 ]. In this study, we discovered that residue I26, associated with the C terminus (residues 21 to 31), which contains the fibril core of hIAPP fiber, represents an extra binding region for disordered oligomers.…”
Section: Discussionmentioning
confidence: 99%
“…The significant roles of lipid acyl chain unsaturation, headgroup charge, and CHOL in partially disordered and fibrillar hIAPP–lipid interactions and membrane permeabilization have been investigated in various lipid mixtures. Overall, hIAPP monomers or oligomers strongly bind to anionic lipids, partially because of the net +2e charge of hIAPP, and prefer unsaturated lipids over saturated lipids [ 6 , 24 , 25 , 26 ]. Experimentally, using a raft-like model membrane containing a zwitterionic PC similar to the raft membrane in this study, the presence of CHOL enhances membrane leakage with pore formation but suppresses fiber growth on membrane surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…al . [44] showed that C-terminal hydrophobic residues of islet amyloid polypeptide (IAPP) can be inserted in the membrane, while Antonschmidt et. al.…”
Section: Discussionmentioning
confidence: 99%
“…al . [41] showed that C-terminal hydrophobic residues of islet amyloid polypeptide (IAPP) can be inserted in the membrane, while Antonschmidt et. al .…”
Section: Discussionmentioning
confidence: 99%